Leptin prevents apoptosis of trophoblastic cells by activation of MAPK pathway - Pérez Pérez, Antonio (2008)
Leptin (Ob), the peripheral signal produced by the adipocyte to regulate energy metabolism, can also be produced by placenta, where it may work as an autocrine hormone. Recently, we have demonstrated that leptin promotes proliferation and survival of trophoblastic cells. In the present work we aimed to study the signal transduction pathways that mediate the trophic effect of leptin in placenta, by using the human placenta choriocarcinoma JEG-3 cell line, as well as trophoblastic cells from human placenta. We have assayed the early phase of apoptosis, triggered by serum deprivation, by using Annexin V-propidium iodide (PI) labeling and flow cytometric analysis, as well as the late phase of apoptosis by studying the activation of caspase-3. We have studied the major signalling pathways known to be triggered by the leptin receptor, and we have investigated the relative importance of these pathways in the effect of leptin by using pharmacological inhibitors. We have found that leptin stimulates Janus kinase (JAK)-signal transducers and activators of transcription (STAT) pathway by promoting JAK-2 and STAT-3 tyrosine phosphorylation. We have also demonstrated the activation of mitogen-activated protein kinase (MAPK) pathway by studying phosphorylation of extracellular-signal regulated kinase (Erk) kinase (MEK) and Erk1/2. PI3K pathway is also triggered by leptin stimulation as assessed by the study of protein kinase B (PKB) phosphorylation. These signaling pathways were confirmed in trophoblastic cells obtained from placenta of healthy donors. The effect of leptin on JEG-3 survival was completely reversed by blocking Erk1/2 activation employing the MEK inhibitor PD98059, whereas it was not affected by PI3K inhibition using wortmannin. These data suggest that the leptin antiapoptotic effect in placenta is mediated by the MAPK pathway.